Infrared tracking system for immersive virtual environments - Gaspar, F. (2021)
In this paper, we describe the theoretical foundations and engineering approach of an infrared-optical tracking system specially design for large scale immersive virtual environments (VE) or augmented reality (AR) settings. The system described is capable of tracking independent retro-reflective markers arranged in a 3D structure (ar-tefact) in real time (25Hz), recovering all possible 6 Degrees of Freedom (DOF). These artefacts can be ad-justed to the user’s stereo glasses to track his/her pose while immersed in the VE or AR, or can be used as a 3D input device. The hardware configuration consists in 4 shutter-synchronized cameras attached with band-pass infrared filters and the artefacts are illuminated by infrared array-emitters. The system was specially designed to fit a room with sizes of 5.7m x 2.7m x 3.4 m, which match the dimensions of the CAVE-Hollowspace of Lousal where the system will be deployed. Pilot lab results have shown a latency of 40ms in tracking the pose of two ar-tefacts with 4 infrared markers, achieving a frame-rate of 24.80 fps and showing a mean accuracy of 0.93mm/0.52º and a mean precision of 0.08mm/0.04º, respectively, in overall translation/rotation DOFs, fulfill-ing the system requirements initially defined.